HEALTH RISK ANALYSIS, RELATED TO THE USE OF MOBILE PHONES - Ураимжон Усманов (Galaxy International Interdisciplinary Research Journal, 2023)
As mobile device users grow, natural questions arise about their impact on people’s health. In recent decades, the International Agency for Research on Cancer has regularly reviewed scientific and experimental evidence on the possibility of carcinogenic exposure to radiation emanating from mobile phones.